2018
DOI: 10.5598/imafungus.2018.09.02.01
|View full text |Cite
|
Sign up to set email alerts
|

The MSDIN family in amanitin-producing mushrooms and evolution of the prolyl oligopeptidase genes

Abstract: The biosynthetic pathway for amanitins and related cyclic peptides in deadly Amanita (Amanitaceae) mushrooms represents the first known ribosomal cyclic peptide pathway in the Fungi. Amanitins are found outside of the genus in distantly related agarics Galerina (Strophariaceae) and Lepiota (Agaricaceae). A long-standing question in the field persists: why is this pathway present in these phylogenetically disjunct agarics? Two deadly mushrooms, A. pallidorosea and A. subjunquillea, were deep sequenced, and sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(64 citation statements)
references
References 70 publications
3
60
1
Order By: Relevance
“…It has been reported that HGT is very common in prokaryotes and can be an important source of their biological evolution, and HGT also occurs in eukaryotes at a lower frequency than that in prokaryotes [29][30][31][32]. The latest reports suggest that HGT may be responsible for the α-amanitin biosynthetic pathway found in the three distantly-related genera Amanita, Galerina and Lepiota [8,9]. It has been reported that in amanitin-producing mushrooms, the POPB gene catalyzes the cleavage and cyclization of the toxin precursor peptide, while the POPA gene is a housekeeping gene unrelated to toxin biosynthesis [7,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that HGT is very common in prokaryotes and can be an important source of their biological evolution, and HGT also occurs in eukaryotes at a lower frequency than that in prokaryotes [29][30][31][32]. The latest reports suggest that HGT may be responsible for the α-amanitin biosynthetic pathway found in the three distantly-related genera Amanita, Galerina and Lepiota [8,9]. It has been reported that in amanitin-producing mushrooms, the POPB gene catalyzes the cleavage and cyclization of the toxin precursor peptide, while the POPA gene is a housekeeping gene unrelated to toxin biosynthesis [7,12].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pulman et al (2016) showed by generating draft genome sequences of A. palloides and A. bisporigera that both possessed approximately 30 members of the MSDIN family, but only three of these genes were common to both [6]. Luo et al (2018) found 18 and 22 MSDIN genes in the A. subjunquillea and A. pallidorosea genomes through PacBio and Illumina sequencing, respectively [8]. However, the MSDIN genes of many Amanita, Galerina and Lepiota amanitin-containing mushrooms have not been investigated in depth to date.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…unigenes. BLAST search against the transcriptome with MSDINs from the two As genomes produced 24 MSDINs, four more than those in our previous result [14]. These four sequences were used as queries to re-search the genome, and the result confirmed their presence ( In order to determine amino acid composition of CylG1 and CylG2, the candidate cyclic peptides were submitted to LC-MS/MS.…”
Section: Transcriptome Of Asmentioning
confidence: 94%
“…To achieve mature state of the toxins, many of these resultant cyclic peptides need to undergo further posttranslational modifications, mainly including multiple hydroxylations, sulfoxidation, epimerization, and formation of a cross-bridge between Trp and Cys, in which order these reactions occur is unknown. The MSDIN genes encoding amatoxins, such as α-and β-amanitins, and phallotoxins, such as phallacidin and phalloidin, are readily found in the sequenced genomes of lethal Amanita species [11,14]. In addition, there are 20 to 30 other unknown MSDIN genes discovered in each of these genomes.…”
Section: Introductionmentioning
confidence: 99%